From biogenic silica and organic matter to authigenic clays and dolomite: Insights from Messinian (upper Miocene) sediments of the Northern Mediterranean. Issue 2 (8th December 2022) - Pellegrino, Luca; Natalicchio, Marcello; Birgel, Daniel; Pastero, Linda; Carnevale, Giorgio; Jordan, Richard W.; Peckmann, Jörn; Zanellato, Nicolò; Dela Pierre, Francesco
Abstract: The biogeochemical cycles of carbon and silicon are tightly coupled in modern marine environments due to the pivotal role of planktonic diatoms. Once diatoms are sedimented, the fate of organic matter and biogenic silica is initially governed by bottom water oxygen levels and bacterial communities involved in remineralization processes. The early diagenesis of biosiliceous sediments may result in drastic changes in composition, sometimes hampering palaeoenvironmental reconstruction. Sedimentary successions deposited in the Mediterranean region during the Messinian salinity crisis (5.97–5.33 Ma) allow to explore the early diagenetic transformation of organic matter and biogenic silica in a restricted basin experiencing a severe palaeoceanographic turnover. Sedimentological and petrographic observations coupled to elemental, mineralogical, inorganic and organic geochemical analyses were carried out on biosiliceous (diatomaceous shales and diatom‐bearing mudstones) and associated clay‐rich and dolomite‐rich sediments (dolomitic mudstones) interbedded with primary gypsum layers in the Piedmont Basin (north‐west Italy). The state of preservation of biogenic silica was governed by different pathways of organic matter remineralization, depending on bottom and pore water redox conditions, which were controlled by the structure of the water column. Aerobic respiration of organic matter in a mixed water column and an oxygenated seafloor promoted biogenic silica preservation. In contrast, bottom water anoxia induced by permanent stratification of the water column favoured the concomitant formation of dolomite and authigenic clays. In particular, organic matter degradation through bacterial sulphate reduction increased pore water alkalinity, promoting the precipitation of dolomite. At the same time, the rise in pH promoted the dissolution of biogenic silica which, reacting with pore water cations, ultimately caused the formation of authigenic clays. This study suggests that the apparent annihilation of Mediterranean marine biota during the Messinian salinity crisis partially reflects an early diagenetic bias produced by interactions of the carbon, silicon and sulphur biogeochemical cycles in a restricted basin.